Penggunaan Algoritma K-Means Pada Aplikasi Pemetaaan Klaster Daerah Pariwisata - Lion Ferdinand Marini; Christian Dwi Suhendra (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The Teluk Wondama Regency has various potentials in the field of religious and natural tourism. There are 13 districts in Teluk Wondama, where some districts are included in the Teluk Cendrawasih National Park area. This makes Teluk Wondama regency visited by many tourists every year. However, this potential is not well maximized by the local government. This is due to the long distance between each district, with a travel time of about 1-2 hours. This research will group districts that have potential to be maximized by the local government using the K-Means clustering algorithm. This algorithm will use the Elbow and Silhouette methods in the process of determining the most ideal cluster. The cluster results obtained will be presented in the form of web-based tourism area maps. The results obtained from the two cluster determination methods are 2 clusters. Of the 13 districts, after the normalization process is carried out by removing districts that do not have tourist data, only 7 districts remain. Based on the cluster analysis, there are 3 districts in cluster 1 and 5 districts in cluster 2. The cluster of tourism areas is presented in the form of a map created using the Shiny Web with R programming language.